Snakebite envenomation in the Caribbean: the role of medical and scientific cooperation - Resiere, Dabor (2018)
Snakebite envenomation by viperid species constitutes a significant public health problem in the Caribbean, causing local tissue damage, systemic complications, and in some cases, severe thrombotic events. Despite being a neglected tropical disease recently recognized by the WHO, snakebite management is hampered by limited access to antivenoms in several countries, leading to high morbidity and mortality. This review emphasizes the urgent need for a coordinated regional strategy to reduce the burden of envenomations, which should include scientific research on venom biology, preclinical evaluation of antivenoms, epidemiological studies, culturally tailored prevention programs, clinical investigations, health professional training, community education, and the establishment of poison control centers. Additionally, socioeconomic, ecological, and cultural factors affecting snake populations and human interactions must be addressed. Strengthening regional scientific and medical cooperation is essential for improving snakebite management, safeguarding public health, and promoting the conservation and study of venomous snakes as part of the Caribbean’s natural heritage.